2021
DOI: 10.1017/s1047951121004753
|View full text |Cite
|
Sign up to set email alerts
|

Workforce demographics and unit structure in paediatric cardiac critical care in the United States

Abstract: Objective: To assess current demographics and duties of physicians as well as the structure of paediatric cardiac critical care in the United States. Design: REDCap surveys were sent by email from May till August 2019 to medical directors (“directors”) of critical care units at the 120 United States centres submitting data to the Society of Thoracic Surgeons Congenital Heart Surgery Database and to associated faculty from centres that provided email lists. Faculty and directors were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Combining website and survey-based data, we demonstrated that United States paediatric critical care medicine fellowships provide vastly different cardiac Prior literature reporting the landscape of cardiac ICU care modelsdesignated cardiac ICU versus mixed paediatric ICUs is sparse, with a recent study reporting 67% designated cardiac ICUs. 2,5,13 Our study demonstrates that 76% (31/41) of responding programmes now have a dedicated cardiac ICU. The learner experience is different in these dedicated cardiac ICUs by nature of unit organisation.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Combining website and survey-based data, we demonstrated that United States paediatric critical care medicine fellowships provide vastly different cardiac Prior literature reporting the landscape of cardiac ICU care modelsdesignated cardiac ICU versus mixed paediatric ICUs is sparse, with a recent study reporting 67% designated cardiac ICUs. 2,5,13 Our study demonstrates that 76% (31/41) of responding programmes now have a dedicated cardiac ICU. The learner experience is different in these dedicated cardiac ICUs by nature of unit organisation.…”
Section: Discussionmentioning
confidence: 76%
“…18,19 There is no standard Accreditation Council of Graduate Medical Education-recommended cardiac curriculum for paediatric critical care medicine fellowships and variable cardiac ICU training pathways post-paediatric critical care medicine fellowship. 2,3,20 However, according to the Pediatric Cardiac Intensive Care Society, either the 1-year paediatric cardiac critical care fellowship or dual boarding in Cardiology and paediatric critical care medicine are now the national standard for training for current fellows undergoing training and expecting to care for cardiac critical care patients. 21 Cardiac ICU experiences during paediatric critical care medicine fellowship also vary in terms of time spent on service (for those with separate units) and institution-specific cardiac didactics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations